In defense of free speech in universities : a study of three jurisdictions - Lai, Amy Tak-Yee, 1977- (University of Michigan Press, 2023)
Amy Lai examines the current free speech crisis in Western universities. She studies the origin, history, and importance of freedom of speech in the university setting, and addresses the relevance and pitfalls of political correctness and microaggressions on campuses, where laws on harassment, discrimination, and hate speech are already in place, along with other concepts that have gained currency in the free speech debate, including deplatforming, trigger warning, and safe space. Looking at numerous free speech disputes in the United Kingdom, the United States, and Canada, the book argues for the equal application of the free speech principle to all expressions to facilitate respectful debates. All in all, it affirms that the right to free expression is a natural right essential to the pursuit of truth, democratic governance, and self-development, and this right is nowhere more important than in the university.